Depression and its associated factors among elderly with type 2 diabetes mellitus - Radzi, Azniza Muhamad (2016)
Introduction: The prevalence of Diabetes Mellitus in elderly is escalating. Depression although carries high mortality and morbidity is often under diagnosed and undertreated. Furthermore elderly with diabetes has higher chance to have depression compared to those who are not. Objectives: To determine the proportion of depression and its associated factors among elderly with Type 2 Diabetes Mellitus in Sungai Petani, Kedah. Methodology: A cross-sectional study involving 509 elderly with type 2 Diabetes Mellitus age 60 and more. Systematic random sampling 1:3 was applied to elderly patients attended Klinik Kesihatan Bandar, Sungai Petani from November 2015 to January 2016. The inclusion criteria were patients who were diagnosed with Type 2 Diabetes Mellitus. The exclusion criteria were cognitive impairment, ECAQ score 5 and less, presence of organic brain syndrome, presence of severe mental disorder like schizophrenia, patients with mental retardation and patients who either deaf or mute. A self-administered questionnaire and participant’s case note were used to obtain the information needed. Malay version of Geriatric Depression Scale (M-GDS-14) was used to assess the depressive symptoms. The data was analyzed using descriptive statistic and multiple logistic regressions. Results: The median age of the respondents was 65 (8.0) years old. Half of respondents were male (54%) and 236 (46%) were female. Majority of respondent were Malays (63.3%) followed by Indians (27.3%) and Chinese (9.4%). Majority of respondents were married (76.8%), some were widows/divorced (21%) while the remaining were single (2.2%). Morethan half were retired (68.2%), 23.4% were never employed and only small numbers of them who were still working (8.4%). Only small number of respondents completed their tertiary education (16.3%), many had completed their secondary schools (39.7%), while the remaining only had their education at primary school level (34.8%) or they did not received formal education (9.2%). Majority of the respondents (67.4%) had household income of less than RM1000. The proportion of depression was 32.2%. Elderly living with children -1.62(p=0.002, 95%CI 0.07, 0.55), Elderly living with spouse, children, in law & grandchildren 1.08(p=0.021, 95%CI 1.18, 7.37), diabetic complication 4.68(p=0.001, 95%CI 2.63, 8.35) and HbA1c 1.23(p=< 0.001, 95%CI 1.09, 1.39) are significantly associated with depression. Conclusion: Depression is high among elderly with Type 2 Diabetes Mellitus. Living arrangement, diabetic complication and HbA1c were significantly associated with depression.